2012
DOI: 10.1073/pnas.1115105109
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide excision repair (NER) machinery recruitment by the transcription-repair coupling factor involves unmasking of a conserved intramolecular interface

Abstract: Transcription-coupled DNA repair targets DNA lesions that block progression of elongating RNA polymerases. In bacteria, the transcription-repair coupling factor (TRCF; also known as Mfd) SF2 ATPase recognizes RNA polymerase stalled at a site of DNA damage, removes the enzyme from the DNA, and recruits the Uvr(A)BC nucleotide excision repair machinery via UvrA binding. Previous studies of TRCF revealed a molecular architecture incompatible with UvrA binding, leaving its recruitment mechanism unclear. Here, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(106 citation statements)
references
References 39 publications
4
102
0
Order By: Relevance
“…The first catalytic step, which is relatively slow, could be explained by some major conformational changes of Mfd, dependent on ATP, allowing the unmasking of UvrA binding surface at the level of the Mfd D2-D7 domain (consistent with the recent SAXS -Small-angle X-ray scattering -results). 36,37 This idea is also supported by the observations that (i) a second RNA polymerase could only bind the promoter when the first RNA polymerase is trapped in this long-lived polymerases, 24 are not able to displace a DNA-lesion-dependent stalled-RNA polymerase. 25,26 Second, Mfd recruits UvrAB, allowing active DNA-lesion repair.…”
Section: Acknowledgmentssupporting
confidence: 65%
“…The first catalytic step, which is relatively slow, could be explained by some major conformational changes of Mfd, dependent on ATP, allowing the unmasking of UvrA binding surface at the level of the Mfd D2-D7 domain (consistent with the recent SAXS -Small-angle X-ray scattering -results). 36,37 This idea is also supported by the observations that (i) a second RNA polymerase could only bind the promoter when the first RNA polymerase is trapped in this long-lived polymerases, 24 are not able to displace a DNA-lesion-dependent stalled-RNA polymerase. 25,26 Second, Mfd recruits UvrAB, allowing active DNA-lesion repair.…”
Section: Acknowledgmentssupporting
confidence: 65%
“…Cultures were subjected to osmotic stress (15% NaCl), acid stress (pH 4.0), cold stress (-20°C) and Heat stress (46°C) for various times and the survival rate was determined thus initiating dissociation of the RNA polymerase ternary elongation complex. The rate of DNA repair depends on many factors, including the cell type, age of the cell, and extracellular environmental conditions (Deaconescu et al 2012). Temperature changes directly affect the growth characteristics of Lactobacillus delbrueckii and lead to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…All of the proteins that are required for global NER are also required for TCR, and the steps subsequent to UvrA dissociation are thought to be common to the two pathways (9). Mfd and UvrB both interact with the same surface of UvrA, and the interaction between Mfd and UvrA involves a region of Mfd that is structurally homologous to part of UvrB (12,13). Mutational analysis of UvrA has shown that the ability of UvrA to distinguish between damaged and undamaged DNA is less important during TCR than during global NER (12), but the mechanism by which the Mfd-UvrA interaction accelerates repair is not understood.…”
mentioning
confidence: 99%
“…Mfd also interacts with the UvrA protein, which is a component of the global NER apparatus (9,12,13). During global NER, damage is detected by a search complex made up of a UvrA dimer and two molecules of the repair protein UvrB.…”
mentioning
confidence: 99%
See 1 more Smart Citation